Sekolah Pascasarjana IPB, Gedung Rektorat Lantai I Kampus IPB Darmaga, Bogor 16680 Telp. 0251-629060, 622642 ext. 161 Fax. 0251-622986 e-mail: forum_pascasarjana@bima.ipb.ac.id - Forum Pascasarjana (Forum Pasca Sarjana, 2008)
Sekolah Pascasarjana IPB, Gedung Rektorat Lantai I Kampus IPB Darmaga, Bogor 16680 Telp. 0251-629060, 622642 ext. 161 Fax. 0251-622986 e-mail: forum_pascasarjana@bima.ipb.ac.id